Screening and optimising metal salt concentration for marine microalgae harvesting by flocculation - Nur Anis, Saarani (2012)
Biodiesel is one of the most renewable fuels that are non-toxic and biodegradable.Demand of biodiesel is constantly increasing as the reservoir of fossil fuel are depleting.The microalgae biomass with high oil content is significant as a sustainable resource for biodiesel production. Production of biodiesel using microalgae biomass appears to be a feasible alternative because there is no conflict with food supply compared with the first generation biofuels, such as oil crops and animal fat. This report deals with the screening and optimisation of metal salts for harvesting marine microalgae by flocculation. The metal salts studies are ferric chloride, aluminium sulphate and ferric sulphate.Wild Nannochloropsis strains of microalgae were cultivated aseptically in sea water for 7 days, after that the microalgae was harvested by using flocculation step with different concentration of metal salt. In order to monitor the efficiency of the metal salt,the turbidity region of microalgae in glass cylinder before and after flocculation was observed. Besides that cell dry weight and FAME (Fatty Acid Methyl Ester) produced was also compared for three flocculation agent used.The most efficient metal saltwash then further optimized for its best performed concentration and pH.Chloride salts (FeCl3) was found to be more efficient in comparison with sulfate salts (Al2 (SO4)3 and Fe2(SO4)3)in harvesting microalgae. FeCl3 gives the highest flocculation efficiency, cell dry weight and FAME production whichare99.3%,0.0791g, 44.3% at 1.0 M concentration of FeCl respectively.Ferric Chloride Was further optimized, where the optimum pH and concentration of FeCl3 are 7.5and 0.9M,with flocculation efficiency of 89.3%, cell dry weight of 3.5g and FAME production 43.3%.In conclusion 0.9 M ferric chloride salt at pH 7.5 is optimum in harvesting microalgae by flocculation.